Validation of predictive equations to assess energy expenditure in acute spinal cord injury. Issue 5 (November 2018) - Ramirez, Christine L.; Pelekhaty, Stacy; Massetti, Jennifer M.; Galvagno, Samuel; Harmon, Laura; Botwinick, Isadora; Scalea, Thomas M.; Stein, Deborah M.
Abstract : BACKGROUND: Acute spinal cord injury (SCI) is devastating with morbidities compounded by inadequate nutrition. The American Society for Parenteral and Enteral Nutrition recommends indirect calorimetry (IC) to evaluate energy needs in SCI because no predictive energy equations have been validated. We sought to determine the accuracy of predictive equations to predict measured energy expenditure (MEE). METHODS: A retrospective review was performed over 2 years. Patients 18 years or older with cervical SCI who received IC were included. Height, weight, maximum temperature and minute ventilation on day of IC, plus MEE and VCO2 from IC were obtained. Predicted energy expenditure (PEE) was calculated using Harris–Benedict (HB), Penn State (PS), Mifflin St. Jeor (MSJ), Weir, Ireton–Jones (IJ), and 25 kcal/kg formulas. MEE was then compared to the PEE of each method. RESULTS: Thirty-nine IC studies were completed for 20 patients. Weir had the strongest correlation to MEE ( r = 0.98), followed by PS ( r = 0.82). Correlations were similar among HB ( r = 0.78), MSJ ( r = 0.75), and IJ ( r = 0.73), and weakest with 24 kcal/kg ( r = 0.55). All had a p value <0.001. Deming regression confirmed strong correlations between Weir and PS to MEE, with coefficients of 1.03 and 1.515 ( p < 0.001), respectively. Other formulas had comparatively higher coefficients and standard errors. Bland–Altman analysis confirmed Weir had the narrowest range of difference, with a mean difference of 25.5 kcal/day, followed by PS (−336.1 kcal/day). CONCLUSIONS: Weir is the best predictive energy equation, with all statistical tests demonstrating a strong correlation between MEE and Weir. The second best predictive equation is the Penn State formula, which predicts actual MEE measured by IC with high accuracy. LEVEL OF EVIDENCE: Diagnostic study, level III